Sexuality and Globalization: An Introduction to a Phenomenology of Sexualities - Bibard, Laurent; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2014)
The book argues that a universally widespread virility currently prevents humans from realizing their sexualities, which are originally the feminine and the masculine. This obstacle may be traced back to Renaissance humanism, whose core intention is to take control over the so-called'nature.'.
Keywords: Political science; World history; Political theory; Political philosophy; Sociology; Sex (Psychology).; Gender expression; Gender identity; Political Science and International Relations; Political Theory; Political Philosophy; Political Science; Gender Studies; Sociology, general; World History, Global and Transnational History